Development of genus-specific universal primers for the detection of flaviviruses - Daidoji, Tomo; Morales Vargas, Ronald Enrique; Hagiwara, Katsuro; Arai, Yasuha; Watanabe, Yohei; Nishioka, Keisuke; Murakoshi, Fumi; Garan, Kotaro; Sadakane, Hiroki; Nakaya, Takaaki (Virology journal, 2021)
Flaviviruses are representative arboviruses carried by arthropods and/or vertebrates; these viruses can pose a public health concern in many countries. By contrast, it is known that a novel virus group called insect-specific flaviviruses (ISFs) also infects arthropods, although no such virus has yet been isolated from vertebrates. The characteristics of ISFs, which affect replication of human-pathogenic flaviviruses within co-infected mosquito cells or mosquitoes without affecting the mosquitoes themselves, mean that we should pay attention to both ISFs and human-pathogenic flaviviruses, despite the fact that ISFs appear not to be directly hazardous to human health. To assess the risk of diseases caused by flaviviruses, and to better understand their ecology, it is necessary to know the extent to which flaviviruses are harbored by arthropods. We developed a novel universal primer for use in a PCR-based system to detect a broad range of flaviviruses. We then evaluated its performance. The utility of the novel primer pair was evaluated in a PCR assay using artificially synthesized oligonucleotides derived from a template viral genome sequence. The utility of the primer pair was also examined by reverse transcription PCR (RT-PCR) using cDNA templates prepared from virus-infected cells or crude supernatants prepared from virus-containing mosquito homogenates. The novel primer pair amplified the flavivirus NS5 sequence (artificially synthesized) in all samples tested (six species of flavivirus that can cause infectious diseases in humans, and flaviviruses harbored by insects). In addition, the novel primer pair detected viral genomes in cDNA templates prepared from mosquito cells infected with live flavivirus under different infectious conditions. Finally, the viral genome was detected with high sensitivity in crude supernatants prepared from pooled mosquito homogenates. This PCR system based on a novel primer pair makes it possible to detect arthropod-borne flaviviruses worldwide (the primer pair even detected viruses belonging to different genetic subgroups). As such, an assay based on this primer pair may help to improve public health and safety, as well as increase our understanding of flavivirus ecology.